2020
DOI: 10.18203/2320-6012.ijrms20200239
|View full text |Cite
|
Sign up to set email alerts
|

Improved breastfeeding with back massage among postnatal mothers

Abstract: Background:The achieving target of exclusive breast milk in Indonesia has not been achieved. The unsuccessful approval of exclusive breastfeeding is partly due to the mother's reasons for the inadequacy of milk production. Physiologically, oxytocin and prolactin are responsible for the smooth production of breast milk. The release of the hormone oxytocin in addition to being transferred by stimulation to the nipple through the baby's mouth or through spinal massage. Application of back massage techniques or ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…The procedure for searching and reviewing literature can be seen in Figure 1. Based on research on increasing breastfeeding by massage on the back to the sixth rib provides a comforting effect, the results of the Reapeated Anova statistical test obtained a value of F = 17.15, p = 0.000 (p <0.005) meaning that there is an effect of back massage on milk production in postpartum , because increased comfort and relaxation in the which is stimulated by the release of the reflex hormone oxytocin endorphins (8). massage intervention group with a p value = 0.021.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure for searching and reviewing literature can be seen in Figure 1. Based on research on increasing breastfeeding by massage on the back to the sixth rib provides a comforting effect, the results of the Reapeated Anova statistical test obtained a value of F = 17.15, p = 0.000 (p <0.005) meaning that there is an effect of back massage on milk production in postpartum , because increased comfort and relaxation in the which is stimulated by the release of the reflex hormone oxytocin endorphins (8). massage intervention group with a p value = 0.021.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that combining oxytocin massage with lavender aromatherapy, music, or acupressure can positively influence breast milk production in postpartum mothers (Kasad, Harahap, Nurdahliana, & Noviyanti, 2022). Breast milk production typically follows the principle of supply and demand during breastfeeding, where frequent emptying and suckling of the breast by the baby lead to increased production (Widiastuti, & Widiani, 2020). However, this principle doesn't apply during the initial 1-3 days post-birth.…”
Section: Discussionmentioning
confidence: 99%
“…The factor that influences breast milk is the hormone prolactin, which is a lactogenic hormone that stimulates the mammary glands to produce breast milk 4 . A decrease in breast milk production during the postpartum period after giving birth can be caused by a lack of stimulation of prolactin and oxytocin, which play a very important role in the smooth production of breast milk 5,6 . The release of prolactin is stimulated by the sensory nerves, which are then sent via the anterior pituitary.…”
Section: Introductionmentioning
confidence: 99%